Strong z°-Submodules of a Module - Faranak Farshadifar (Journal of Mathematics)
Let R be a commutative ring with an identity. The purpose of this paper is to introduce and investigate the notion of strong z°-submodules of an R-module as an extension of z°-submodules and quasi z°-submodules.